1996
DOI: 10.1007/bf02072536
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetics of uncleaved oocytes and arrested zygotes in IVF programs

Abstract: Of uncleaved oocytes without a polar body, 39% were judged cytogenetically abnormal (17% unbalanced predivision and 21.5% diploid). Of 575 oocytes with a polar body, 124 (21.5%) showed numerical or structural chromosome aberrations. In arrested zygotes, approximately equal cases were found with separate condensed haploid complements (no syngamy), nuclear asynchrony and pulverized DNA, and apparently cytogenetically normal zygotes arrested at mitosis. These data on chromosome abnormalities were also analyzed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 25 publications
2
16
0
1
Order By: Relevance
“…In contrast, Angell (1997) found only single chromatids in addition to, or replacing, whole chromosomes, and Verlinsky et al (1996b) observed chromatid malsegregation more frequently than chromosome nondisjunction. The remaining studies have reported only nondisjunction events (Martin et al, 1986;Veiga et al, 1987;Bongso et al, 1988;Djalali et al, 1988;Pellestor and Sèle, 1988;Papadopoulos et al, 1989;Macas et al, 1990;Tarín et al, 1991;Zenzes et al, 1992;Almeida and Bolton, 1994;Ma et al, 1994;Roberts and O'Neill, 1995;Benkhalifa et al, 1996). We found that the chromosomes more frequently involved in aneuploidy events were those of group D (45.5 %), according to other authors (Djalali et al, 1988;Macas et al, 1990;Zenzes et al, 1992;Kamiguchi et al, 1993).…”
Section: Discussionsupporting
confidence: 59%
“…In contrast, Angell (1997) found only single chromatids in addition to, or replacing, whole chromosomes, and Verlinsky et al (1996b) observed chromatid malsegregation more frequently than chromosome nondisjunction. The remaining studies have reported only nondisjunction events (Martin et al, 1986;Veiga et al, 1987;Bongso et al, 1988;Djalali et al, 1988;Pellestor and Sèle, 1988;Papadopoulos et al, 1989;Macas et al, 1990;Tarín et al, 1991;Zenzes et al, 1992;Almeida and Bolton, 1994;Ma et al, 1994;Roberts and O'Neill, 1995;Benkhalifa et al, 1996). We found that the chromosomes more frequently involved in aneuploidy events were those of group D (45.5 %), according to other authors (Djalali et al, 1988;Macas et al, 1990;Zenzes et al, 1992;Kamiguchi et al, 1993).…”
Section: Discussionsupporting
confidence: 59%
“…In addition, prolonged culture has been suggested to allow the selection of chromosomally competent embryos, because embryos failing to develop more often show multiple aneuploidy [23,24]. However, the possible influences of an extended embryo culture to the blastocyst stage on the incidence of monozygotic multiples and the cancellation of embryo transfer may be of concern [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…44 Ya pı lan ça lış ma lar da %23 ile %80 ara sın da kro mo zo mal ano ma li nin tes pit edil di ği gös te rilmiş tir. Bu ça lış ma da ise ano ma li li em bri yo la rın ora nı nın %80 ol du ğu gö rül müş ve so nuç lar li te ratür ile uyum lu bu lun muş tur.…”
Section: Medical Geneticsunclassified